A Review on Mechanical Behaviour of Bast-Glass Fibre Based Hybrid Polymer Composites. (2017) - Kumar, Sandeep; Gangil, Brijesh; Prasad, Lalta; Kumar Patel, Vinay
Abstract: Natural fibres are gaining interest as reinforcement for polymer composite due to their environ mental and cost-effective benefits. Bast fibres is a prominent reinforcement for use in polymeric materials because of its low weight and cost, eco -friendly and abundant in nature. Several authors manifest the advantageous usage of cellulosic bast fibres based polymeric materials in automobile industries and structural applications, but certain problems have been observed with the use of such fibres such as high water-uptake tendency and low mechanical strength than the inorganic fibres. The adverse properties of such bast fibres based composites can be overcome by hybridization with synthetic fibres. In the present article, we have reviewed the effect of hybridization of glass fibres on mechanical properties of bast fibre (jute, hemp, kenaf, flax) based hybrid polymer composites.